Difficulties inherent in the United Nations convention on contracts for the international sale of goods (CISG) - Abraham, Deepa Raju (Centre for Law and Society, 2026)
The United Nations Convention on Contracts for the International Sale of Goods (CISG) is increasingly governing the law of international sale of goods.1 The CISG is a multilateral treaty that governs the rights and obligations of parties to international sales contracts. 2 It is designed to foster international trade by making it easier and more economical to buy and sell raw materials, commodities and manufactured goods in trans-national commerce through the adoption of a unified legal approach.